Interprofessional collaboration in primary care: what effect on patient health? A systematic literature review - Bouton, Céline; Journeaux, Manon; Jourdain, Maud; Angibaud, Morgane; Huon, Jean-François; Rat, Cédric (BMC family practice, 2023)
Background In a period of change in the organization of primary care, Interprofessional Collaboration (IPC) is presented as one of the solutions to health issues. Although the number of inter-professional interventions grounded in primary care increases in all developed countries, evidence on the effects of these collaborations on patient-centred outcomes is patchy. The objective of our study was to assess the effects of IPC grounded in the primary care setting on patient-centred outcomes. Methods We conducted a systematic literature review using the PubMed, Embase, PsycINFO and CINAHL databases from 01/01/1995 to 01/03/2021, according to the PRISMA guidelines. Studies reporting the effects of IPC in primary care on patient health outcomes were included. The quality of the studies was assessed using the revised Downs and Black checklist. Results Sixty-five articles concerning 61 interventions were analysed. A total of 43 studies were prospective and randomized. Studies were classified into 3 main categories as follows: 1) studies with patients at cardiovascular risk (28 studies)—including diabetes (18 studies) and arterial hypertension (5 studies); 2) studies including elderly and/or polypathological patients (18 studies); and 3) patients with symptoms of mental or physical disorders (15 studies). The number of included patients varied greatly (from 50 to 312,377). The proportion of studies that reported a positive effect of IPC on patient-centred outcomes was as follows: 23 out of the 28 studies including patients at cardiovascular risk, 8 out of the 18 studies of elderly or polypathological patients, and 11 out of the 12 studies of patients with mental or physical disorders. Conclusions Evidence suggests that IPC is effective in the management of patients at cardiovascular risk. In elderly or polypathological patients and in patients with mental or physical disorders, the number of studies remains very limited, and the results are heterogeneous. Researchers should be encouraged to perform studies based on comparative designs: it would increase evidence on the positive effect and benefits of IPC on patient variables.